Enhancing Geography Teaching Through Technological Knowledge: A Study of Public Secondary Schools in Chanika District, Tanzania - Clement John Maganga; Ashwarya Srivastava (East African Journal of Education Studies, 2026)
This study investigates how technological knowledge (TK) enhances Geography teaching in public secondary schools in Chanika District, Tanzania, by examining the types of technology used, integration strategies, challenges faced, and the role of teacher training. Using a mixed-methods research design, the study combined quantitative surveys (n=60) and qualitative semi-structured interviews (n=12) to explore teachers' experiences with technology integration. The findings highlight gender differences in technology usage, with male teachers utilising more advanced tools like GIS and projectors, while female teachers face barriers such as limited training and resources. The study emphasises the need for curriculum reform, enhanced teacher professional development, and improved technological infrastructure to foster more interactive and student-centred learning environments. It concludes with recommendations for targeted teacher training, investment in technology, and equitable access to resources to improve Geography education and student outcomes in Tanzanian secondary schools.